Relationship between incremental BMI with HbA1c in diabetic and non –diabetic obese patients : Relationship between BMI and HbA1c in diabetes - Rahman, Aparna; Alam, Zahid; Jahan Hoque, Shabnam; Afroz, Farhana (Journal of the Medical College for Women & Hospital, 2024)
Background: The global rise of obesity is alarming, not only for its increasing prevalence but also for its constellation of associated diseases that diminish life quality and expectancy. In developing countries like Bangladesh, tackling obesity-related metabolic and other morbidities pose a significant challenge. Obesity demonstrably strengthens the links between diabetes, hypertension, coronary artery disease, stroke, and even mortality associated with these events. This study investigated the connection between body mass index (BMI) and glycemic status (measured by HbA1c) of both diabetic and non-diabetic obese individuals in Bangladesh, along with the spectrum of morbidities leading to hospitalization. Understanding these connections empower clinicians to prioritize specific management goals and ultimately lessen obesity-related morbidity in this population. Materials and Method: This prospective observational study has been carried out at a tertiary hospital among 50 patients with clinical obesity (BMI > 30 kg/m2 ) and excluded those with pathological causes of obesity, e.g. hypothyroidism, Cushing's syndrome, etc. The anthropometric measurement, glycemic status, and obesity related complications were recorded for all patients. BMI was stratified into three groups, Group I (BMI 30.1-40 kg/m2), Group II (BMI 40.1-50 kg/m2) and Group III (BMI >50 kg/m2) where HbA1c in these groups were compared to find out any association including morbidity. Data analysis was performed with SPSS for windows version 22.0 and then was presented in tables and charts. Results: The cohort included 41 (82.0%) women and 9 (18.0%) men. The mean age of the obese patients was 54.71 years with almost half being in the age group of 51-60 years (46.0%). Majority i.e. 43 (86.0%) of the patients had a BMI ranging from 30.1-40 kg/m2. Among the study subjects, 28 had diabetes mellitus (56%) and the rest were non-diabetic (44%). There was a significant relationship found between HbA1c and BMI of the obese patients with diabetes mellitus (p = 0.009). Scatter diagram showed significant correlation between BMI and HbA1c in obese diabetes patients (r=0.622; p=0.001). Conclusion: This study identified a positive correlation between BMI and HbA1c in diabetic patients, but not in non-diabetic ones. Further research is needed to explore the mechanisms at play in non-diabetic patients with higher BMI. J Med Coll Women Hosp.2024; 20(1): 60-67